Modeling and Simulation of a Hybrid Piezoelectric– Electromagnetic System for Vibration Energy Harvesting - (:unkn) unknown (Springer, 2026)
Vibration energy harvesting is a promising approach for enabling energy autonomy in low-power electronic systems operating under ambient mechanical excitations, particularly in the low-frequency range. This paper presents a coupled analytical and numerical investigation of a hybrid vibration energy harvesting system that integrates piezoelectric and electromag netic transduction mechanisms within a single cantilever-based structure. A reduced-order analytical formulation is introduced to provide physical insight into the strain and velocity-dominated energy conversion mechanisms asso ciated with different vibration modes. In parallel, a Multiphysics finite element model is developed in COMSOL Multiphysics to evaluate the dynamic behavior of the structure and the electrical output of both transducers under harmonic excitation. Numerical simulations show that the piezoelectric transducer achieves its highest performance near the first bending mode at approximately 15 Hz, delivering a maximum output power of 1.7 mW under optimal load conditions. In contrast, the electromagnetic transducer exhibits improved performance at the second resonance frequency near 64 Hz, generating a peak output power of 2.8 mW at a low electrical load resistance. The demonstrate that the hybrid configuration enables effective energy harvesting across multiple vibration modes and enhances adaptability to varying excitation conditions compared to single-mode harvesters. The proposed modeling framework provides a consistent basis for the design and optimization of hybrid vibration energy harvesting systems intended for low power autonomous applications.
Keywords: Vibration energy harvesting, Hybrid energy harvester, Piezo electric transducer, Electromagnetic generator, Multiphysics modeling, Finite element simulation.